Una nueva actitud de la Iglesia ante el mundo de la Gaudium et Spes - González-Carvajal, Luis (Estudios eclesiásticos, 2006)
Until the Second Vatican Council the attitude of the Church and its theology towards the «world», understood as being the accumulation of temporal realities, was characterized by a sort of disregard, even hostility when envisaging the «modern world». This article takes into account the new conception of «world» used by Gaudium et Spes, and brings to the foreground the new relationship betweenthe Church and the world: recognition, acceptation, a humble attitude, dialogue and service.